(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Direct compression is the process of choice for tablet manufacturing due to its simplicity and lesser steps involved. For direct compression, the material of interest should have compressibility and compactibility. The aim of present work to convert valsartan drug powder into crystals those are directly compressible material. Materials and Methods: For the crystallo-co-agglomeration technique process, a system of Dimethylformamide-Water-Dichloromethane as good solvent-poor solvent-bridging liquid is used. Hydroxypropyl cellulose (HPC) was used to stabilize the system. Talc confirms its role as a bulking agent as well as the substrate for the spherical crystals. Results: The spherical crystals obtained in the presence of 0.5% HPC had greater particle size distribution, mechanical strength, compressibility, and compactibility in comparison to pure drug crystals. Drug content of the spherical crystals ranged around 84% and in vitro release for the optimized batch was 98.73%. In vivo bioavailability studies were performed in the Wistar rats, bioavailability (AUC) of the spherical crystals (18.90 ± 3.254 μg/ml*h) was significant (P < 0.05) to the pure drug (13.68 ± 0.902 μg/ml*h), and marketed preparation (17.49 ± 2.5 μg/ml*h). Stability studies in accordance to ICH guidelines indicated stability of the obtained products. Conclusion: Valsartan pure drug crystals were converted into the directly compressible material by crystallo-co-agglomeration technique. The obtained spherical crystals had greater solubility and flowability as compared to the original crystals.